The play pyramid: a play classification and ideation tool for toy design. (21st December 2009) - Kudrowitz, Barry M.; Wallace, David R.
Toy designers and students may benefit from a universal classification system to communicate and ideate new toy concepts. In this paper, we present two graphical tools that help designers to classify and manipulate toy product concepts. The play pyramid is a three-dimensional map that allows designers to classify a toy concept by placing it in a space between what we believe to be four independent axes of play (sensory, fantasy, construction and challenge). The sliding scales of play are modifiers or adjectives that one can use to further describe the play of a toy concept. By taking a toy design and moving it around inside the play pyramid or along the scales of play, the design can take on new and unforeseen play affordances. Both of these tools have been tested and applied in industry sponsored research and design education settings and were successful in expanding upon toy ideas.